SAMARA PERINATAL CENTER: EFFICIENCY OF ACTIVITY AND COMMUNICATION WITH SCIENTIFIC SCHOOL - L. S. Tselkovich; A. S. Benyan; Yu. A. Rudenko; T. A. Tezikova; R. B. Balter; T. V. Ivanova; A. R. Ibragimova; O. A. Ilchenko; G. I. Teleeva; A. Yu. Ryabov; D. L. Pribytkov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The paper studies the main performance indicators of the Samara Perinatal Center over the past three years. Positive dynamics which manifests itself in a decrease in the number of premature births and the number of newborns with extremely low body weight and in a decrease in perinatal mortality and morbidity in newborns is noted. It is emphasized that the positive results in practical medicine are interconnected with the introduction of new scientific approaches to the problems of gestation proposed by scientists and graduate students of Samara State Medical University.